COMPARATIVE ANALYSIS OF BLB RESISTANCE IN RICE GERMPLASM USING MORPHOLOGICAL AND MOLECULAR MARKERS - NAHEED, K; SABAR, M; Ali, Q; ABBAS, A; MUBASHAR, U; AHMAD, S; ASHFAQ, M (Biological and Clinical Sciences Research Journal, 2024)
Rice (Oryza sativa L.) serves as a staple food for billions globally but faces significant challenges from Bacterial Leaf Blight (BLB), caused by Xanthomonas oryzae pv. oryzae. BLB poses a substantial threat to rice production, with potential crop losses reaching up to 75% during severe outbreaks. This study evaluated the morphological and genotypic responses of 25 indica rice genotypes against BLB under field conditions at the Rice Research Institute, Kala Shah Kaku, Sheikhupura, Pakistan, using a Randomized Complete Block Design (RCBD). Phenotypic screening was conducted by inoculating BLB cultures via the leaf clipping method. Fourteen morphological traits, including plant height, number of tiller, panicle length, flag leaf dimensions, stem diameter, grain characteristics, survival rate, damage rate, and 1000-grain weight, were recorded. Molecular characterization was performed for five major BLB resistance QTLs (Xa4, Xa5, Xa21, Xa23, and Xa34). Results revealed 16 resistant genotypes, 4 moderately resistant, 3 moderately susceptible, and 1 highly susceptible. Resistant genotypes, such as 37681, 8060, and 30579, exhibited minimal lesion lengths, ranging from 0.33 cm to 5 cm. These findings highlight promising genotypes for breeding programs aimed at enhancing BLB resistance, with linked molecular markers providing robust tools for future screening and development of BLB-resistant rice varieties.